The Influence of Transformational Leadership on Employee Performance Through Knowledge Sharing: A Study of Hospital Cleaning Service Staff - Nurida Abdul Kadir; Siti Istikhoroh; Mohamad Afrizal Miradji (Publikasi Indonesia, 2025)
Abstract. In the hospital service sector, cleaning service personnel play a vital role in maintaining hygiene standards and overall service quality. This study aims to analyze the influence of transformational leadership on knowledge sharing as a mechanism to improve the performance of hospital cleaning service employees at PT ISS Indonesia, Surabaya Branch. The research method used is a quantitative approach with an explanatory research design. Data were obtained through questionnaires distributed to 109 respondents, determined using the Slovin formula. Data analysis was performed using the Structural Equation Modeling (SEM) method with SmartPLS 3.0 software. The results of the study show that (1) transformational leadership has a significant effect on knowledge sharing, (2) knowledge sharing has a significant effect on employee performance, (3) transformational leadership has a significant effect on employee performance, and (4) knowledge sharing significantly mediates the relationship between transformational leadership and employee performance. These findings confirm that transformational leadership not only has a direct impact on performance but also enhances it through a culture of knowledge sharing. The implications of this study highlight the importance of implementing a transformational leadership style that promotes openness, trust, and a culture of information sharing within the operational work environment. This approach can continuously improve the effectiveness, service quality, and productivity of cleaning service employees.